Ethnic and gender-based prejudice towards medical doctors? The relationship between physicians' ethnicity, gender, and ratings on a physician rating website. Issue 5 (3rd September 2022) - Kauff, Mathias; Anslinger, Julian; Christ, Oliver; Niemann, Moritz; Geierhos, Michaela; Huster, Lars
ABSTRACT: We investigated manifestations of ethnic and gender-based prejudice in a rather understudied high-status environment, that is we studied biased ratings of physicians with a migration background and female physicians. In a preregistered, archival study, we analyzed ratings of more than 140, 000 physicians on a German rating website for medical professionals. Results indicate that general practitioners (but not dentists or specialists) with non-German names are rated less favorably than general practitioners with German names. This effect did not vary across regional contexts with varying prosperity and diversity. Our analyses also revealed that female physicians are evaluated less positively than male physicians. Contrary to our assumptions, bias against female physicians was especially strong in medical sub-disciplines that are characterized by a high share of female physicians.